Analisis Rentang Harga Gula Kristal Rafinasi Pada Pasar Lelang Komoditas Dengan Pendekatan Harga Paritas - Wicaksena, Bagus (Jurnal Borneo Administrator, 2017)
The government has stipulated Trade Minister Regulation Number 16/M-DAG/PER/3/2017 regarding Refined Sugar Trade in Commodity Auction Market. However, the method of determining the highest and the lowest sugar price has not been arranged in the regulation. Thus, this study aims to analyze the price range of Refined Sugar in Commodity Auction Market. Import parity approach of raw sugar is utilized to calculate auction price range. The cost components are highest and lowest raw sugar price in international market as well as tolling fee for production and distribution of refined sugar. The result indicates that the estimated lowest price is between IDR 7,869/Kg and IDR 8,176/Kg and the estimated highest price is between IDR 11,527/Kg and IDR 11,742/Kg. This study recommends that import parity approach of raw sugar can be used to determine the price range of refined sugar. However, technical guidance for seller/buyer with existing sales contracts, technical team consisting representative of stakeholders to anticipate the fluctuating price issue, and the certainty of import quota for raw sugar as supply guarantee of refined sugar in action market are needed to be considered in order to support the regulation. Keywords: Refined Sugar, Auction Market, Parity Price Pemerintah menerbitkan Peraturan Menteri Perdagangan Nomor 16/M-DAG/PER/3/2017 Tentang Perdagangan Gula Kristal Rafinasi (GKR) Melalui Pasar Lelang Komoditas (PLK). Dalam regulasi dimaksud, terdapat 1 (satu) aspek dalam mekanisme lelang yang belum dicapai kesepakatan, yaitu metode penentuan Harga Batas Bawah (HBB) dan Harga Batas Atas (HBA) penjualan GKR. Untuk menganalisis besaran rentang harga lelang GKR, digunakan pendekatan paritas impor GKM dengan komponen harga GKM tertinggi dan terendah, serta biaya tolling terkait produksi dan distribusi GKR. Besaran HBB diperkirakan berada pada kisaran Rp 7.869/Kg dan Rp 8.176/Kg dan HBA sebesar Rp 11.527/Kg dan Rp 11.742/Kg. Sebagai perangkat kebijakan, pendekatan paritas impor GKM dapat digunakan untuk menentukan rentang harga GKR. Namun demikian diperlukan beberapa pertimbangan antara lain petunjuk teknis bagi peserta lelang yang sudah memiliki kontrak penjualan, dukungan tim teknis yang terdiri dari perwakilan pemangku kepentingan untuk mengantisipasi dinamika harga GKM, serta kepastian kuota impor GKM dalam menjamin supply GKR di PLK. Kata Kunci: Gula Rafinasi, Pasar Lelang, Harga Paritas